ANALISIS PEMANFAATAN BUKU CERITA ANAK (HEWAN DAN LINGKUNGANNYA) DALAM PEMBELAJARAN MENGGAMBAR ILUSTRASI SEKOLAH DASAR - Dewi, Anisa Saptya; Gunawan, Dani; Pujiasti, Dea Asri; Adiredja, Rajji Koswara (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
This study aims to describe the use of children's story books in learning to draw illustrations for 5th grade students of SDIT Cokroaminoto Garut. The research subjects were 5th grade students. The research method used in this study was descriptive qualitative. Data collection techniques using observation, interviews, and documentation. The data were analyzed through the stages of data reduction, data presentation and drawing conclusions. The results of research conducted by researchers from the use of children's story books in learning to draw illustrations for the 2021-2022 school year at SDIT Cokroaminoto Garut. Learning evaluation is an assessment carried out on the results of class 5 illustration drawings totaling 40 students with a sufficient percentage of 10% category, 57,5% good category, and 32.5% very good category. Then the obstacles that occur are the lack of concentration of children during learning, the lack of availability of infrastructure